The Role of Brain-Based Learning in Training Students' Critical Thinking Skills - Yuni Rahmawati; Madlazim Madlazim; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to determine the role of brain-based learning in training students' critical thinking skills. Method: The research method used is a review article from 20 main scientific articles obtained from Google Scholar, Google, and Science Direct online with the keywords brain-based learning and critical thinking skills. Results: The results show that brain-based learning can be applied to gain critical thinking skills in mathematics and natural science material compared to conventional learning. Brain-based learning notes how the brain processes and interprets information after processing. A learning method that aligns with how the brain functions naturally will help students become more adept at critical thinking. Novelty: One of the most challenging issues of the 20th century is the improvement of information technology and the environment. Building quality human resources is a strategic and critical function of high-quality education. Today's students need to learn how to think critically.